Peningkatan Motivasi Berwirausaha Melalui Layanan Informasi pada Siswa SMP - Joko Rahyono (Journal Prakarsa Paedagogia, 2018)
The purpose of this study is 1. Describe entrepreneurial motivation for students in Class IX A of SMP Negeri 2 Dukuhseti Pati before and after being provided with information services. 2. Obtaining an increase in entrepreneurial motivation through information services for students of Class IX A of SMP Negeri 2 Dukuhseti Pati in the academic year 2017/2018. The research method consists of: the setting of this research in SMP Negeri 2 Dukuhseti Pati. Characteristics and Subjects of this study were 22 students of Grade IX A who needed increased motivation through information services. The variables of this study consisted of two: independent and bound variables. The free variable information service. The dependent variable is entrepreneurial motivation. The research procedure for guidance and counseling measures uses a continuous cycle, each cycle consisting of the planning, implementation, observation and reflection stages. Data collection techniques used observation and interviews. Data analysis used qualitative analysis and it was processed in a comparative descriptive manner. That is, comparing the first cycle which was known as many as 9 students whose motivation was still low, then after receiving information services in cycle II, a total of 15 students obtained a very motivational category. the height and content of 7 students got high category. The results can be concluded that: 1. Increasing students' entrepreneurial motivation through information services get very good results, this increase can be seen from the low motivation before the service is given to their courage to open their own business after providing information services 2. Student entrepreneurship motivation after attending information services has increased from 43 , 7% (low) to 80.56% (very high), marked by increased observations and results of interviews that showed an increase in students' entrepreneurial skills.